Is self-report sleepiness associated with cognitive performance in temporal lobe epilepsy? - Helena Dresch Vascouto; Maria Emília Rodrigues de Oliveira Thais; Camila Moreira Osório; Juliana Ben; Lucia Sukys Claudino; Alexandre Ademar Hoeller; Hans J. Markowitsch; Peter Wolf; Katia Lin; Roger Walz (Arquivos de Neuro-Psiquiatria)
ABSTRACT Sleepiness and cognitive impairment are common symptoms observed in patients with epilepsy. We investigate whether self-reported sleepiness is associated with cognitive performance in patients with refractory mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS). Seventy-one consecutive patients with MTLE-HS were evaluated with the Stanford Sleepiness Scale (SSS) before neuropsychological evaluation. Their mean SSS scores were compared with controls. Each cognitive test was compared between patients with (SSS ≥ 3) or without sleepiness (SSS < 3). Imbalances were controlled by regression analysis. Patients reported a significantly higher degree of sleepiness than controls (p < 0.0001). After multiple linear regression analysis, only one test (RAVLT total) remained associated with self-reported sleepiness. Conclusion: Self-reported sleepiness was significantly higher in MTLE-HS patients than controls, but did not affect their cognitive performance. If confirmed in other populations, our results may have implications for decision making about sleepiness screening in neuropsychological settings.